2007
DOI: 10.1007/s11605-007-0210-3
|View full text |Cite
|
Sign up to set email alerts
|

COX-2 mRNA Expression is Significantly Increased in Acid-exposed Compared to Nonexposed Squamous Epithelium in Gastroesophageal Reflux Disease

Abstract: In summary our findings suggest that alterations in COX-2 mRNA expression occur independently of endoscopic or histologic signs of GERD in the acid-exposed squamous epithelium of the distal esophagus. However, this early COX-2 increase in GERD is further upregulated within the MDA sequence for yet unknown reasons.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…COX‐2 protein and mRNA expression is induced by bile acids and has also been found to be induced in some malignant processes 20,21 . COX‐2 expression can be induced in cultured human pharyngeal cells by bile, acid or both, implying that LPR may have a role in malignant transformation in the upper aerodigestive tract 18 …”
Section: Discussionmentioning
confidence: 99%
“…COX‐2 protein and mRNA expression is induced by bile acids and has also been found to be induced in some malignant processes 20,21 . COX‐2 expression can be induced in cultured human pharyngeal cells by bile, acid or both, implying that LPR may have a role in malignant transformation in the upper aerodigestive tract 18 …”
Section: Discussionmentioning
confidence: 99%
“…Earlier, studies have reported that COX-2 expression is unregulated in precancerous lesions and preinvasive carcinoma and positively correlates with tumor invasion and lymphatic metastasis (Lurje et al, 2007;Strazisar et al, 2009). Therefore, increasing expression of COX-2 might occur in the early stages of the tumor and the detection of COX-2 level is helpful for early diagnosis of CRC.…”
Section: Introductionmentioning
confidence: 99%
“…SOX9 is also essential in the development of embryonic columnar-lined esophagus but is switched off in postnatal life and is reexpressed again in BM (14,28,49). Expression of cyclooxygenase-2 (COX-2) is upregulated and plays has a key role in the development of BM, possibly by disrupting key signaling pathways that maintain homeostasis in the NES epithelium (22).…”
mentioning
confidence: 99%